2011
DOI: 10.1111/j.1477-2574.2011.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcomes after laparoscopic and open hepatic resection: systematic review and meta-analysis

Abstract: LLR has short-term advantages and seemingly equivalent long-term outcomes and can be considered a feasible alternative to open surgery in experienced hands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
134
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(150 citation statements)
references
References 54 publications
10
134
0
6
Order By: Relevance
“…Note however, that the vast majority of studies were retrospective studies, with no randomised controlled trials, and therefore there may be significant selection bias. Unsurprisingly, these findings echo those of an earlier meta-analysis of 26 studies [38] . However, in relation to oncological outcomes, this meta-analysis analysed HCC outcomes separately to other malignant diseases and found that there was a significant trend for improved overall survival (OR: 1.5 -1.0-2.2; P = 0.049) in the laparoscopic group.…”
Section: Laparoscopic Liver Resectionsupporting
confidence: 85%
“…Note however, that the vast majority of studies were retrospective studies, with no randomised controlled trials, and therefore there may be significant selection bias. Unsurprisingly, these findings echo those of an earlier meta-analysis of 26 studies [38] . However, in relation to oncological outcomes, this meta-analysis analysed HCC outcomes separately to other malignant diseases and found that there was a significant trend for improved overall survival (OR: 1.5 -1.0-2.2; P = 0.049) in the laparoscopic group.…”
Section: Laparoscopic Liver Resectionsupporting
confidence: 85%
“…In a comprehensive meta-analysis study, laparoscopic hepatectomy was compared to open hepatic resection in 1678 patients across 26 studies. While it is associated with longer operating times and no differences in oncological outcomes, it is advantageous in several aspects [3] . Laparoscopic hepatectomy is associated reduced blood loss, decreased portal clamp time, a decrease in overall and liver-specific complications, and shorter postoperative hospital stays [3] .…”
Section: Introductionmentioning
confidence: 99%
“…While it is associated with longer operating times and no differences in oncological outcomes, it is advantageous in several aspects [3] . Laparoscopic hepatectomy is associated reduced blood loss, decreased portal clamp time, a decrease in overall and liver-specific complications, and shorter postoperative hospital stays [3] . Recent technological development of devices and accumulation of experiences have facilitated the expansion of the indication of the procedure [4,5] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these were found to be lower after LLR in 40 and 11 studies, respectively. Twelve meta-analyses and one Cochrane report were also analyzed [35][36][37][38][39][40][41][42][43][44][45][46][47] and consistent results included reduced blood loss and transfusions requirements when studied. This clearly shows that, in selected patients LLR when compared with open surgery is associated with reduced blood loss and subsequent transfusion rates.…”
Section: Discussionmentioning
confidence: 99%